The Coordinates of Covenantal Pluralism: Mapping Pluralist Theory in the 21st Century - Joustra, Robert (The review of faith & international affairs, 2020)
The aim of this article is to map the plurality of pluralist theories, indicate and (hopefully) make sense of what the many important contributions explaining this resurgent notion have been to date, and finally locate “covenantal pluralism” in this developing conversation. The essay plots at least 11 models on a “pluralist quadrant” in order to help us understand their unique contributions to the pluralism debate. Finally, I aim to show in conclusion how an emphasis on covenants captures some of the best of the many discourses about pluralism discussed in the essay, thereby highlighting the advantages of a holistic and balanced approach to conceptualizing normative pluralism.